Symbolic Meaning of Kecak Dance Performance in Balinese Culture - Purnomo P, Rana Anyndya; Nirwan, Nirwan; Fauzi, Makmun (STIBA IEC JAKARTA, 2024)
This research discusses the meaning and significance or semiotic theory of Balinese culture, focusing on a dance called the Kecak Dance. Researchers used descriptive qualitative methods using a semiotic theory approach from Osgood, C. E. Focus on meaning. Mouton. The sources for this research are several journals, videos and local residents. The collection technique in this research is the reading and note taking technique. The results of this research show that (1) There is a spiritual meaning in every Kecak dance movement. (2) There is a meaning that can be called a communication to Sang Hyang or God Almighty. (3) There is a meaning regarding the form of balance like diversity.